ANALISIS REGENERASI IMAM MASJID: DINAMIKA ANTARA IMAM YANG TIDAK MAU DIGANTI DAN PEMBERDAYAAN ANAK MUDA DI DUSUN RA’CAK, DESA MAMPU, KEC. ANGGERAJA, KAB. ENREKANG - Muhammad Akbar; Sefia Sefia; Dewi Fratiwi; Moch Farhan; Dzakwan Sukardi (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2023)
The writing of this research aims to understand the dynamics of the regeneration of the imam of the al Falah mosque in Ra’cak hamlet. Researchers conducted this research with qualitative methods in the form of observation research instruments, interviews from several sources, and literacy studies through several literature sources. This study reveals that the tenure of older imams is the main obstacle in the process of regenerating mosque imams. This study also analyzes the pros and cons related to the replacement of imams who are no longer good at reading qur’an. On the one hand, the regeneration of imams is considered necessary to maintain the quality of worship and empower young people to regenerate as imams. However, on the other hand, the replacement of priest can also trigger social conflict and raise question about respect for elders and question about who will replace them as priests. Therefore, it’s necessary to hold a discussion involving varios related parties, such as mosque administrators, community leaders, and worshipers to find the best solution. Either by replacing the imam with a younger people who has a better quality of reading the qur’an, or asking the old imam to resign honorably and giving appreciation for his services.